Q: What is 4x plus 3y plus x equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

x = 5 y = 2 4x - 3y = ? 4(5) - 3(2) = ? 20 - 6 = 14

4x+3y-2x+y 4x-2x+3y+y 2x+4y Taking out 2 common 2(x+2y) Hence the required answer is 2(x+2y)

(A): 4x + y = 7 (B): 2x - 3y = -7 2*(B) 4x - 6y = -14 Subtract from (A) 7y = 21 Divide both sides by 7: y = 3 Substitute in (A): 4x + 3 = 7 ie 4x = 4 or x = 1 Answer: x = 1 , y = 3

The given equation: =3x-4x plus 9xy-12y =3x-4x+9xy-12y =-x+9xy-12y =-x+3y(3y-4) Answer.

x = 2.15 and y = 3.75

Related questions

4x + 3y=9 x=0 y=3

x = 3 and y = 0

4x + 3y = 6y 4x = 3y 4/3 x = y The slope is 4/3 and the y intercept is 0.

4x + 3y = 7 y = [(-4)/3] x + 7/3

a) 4x+13y=40 b) 4x+3y=-40c) multiply b per(-1)=-4x-3y-40d) sum a and c: 4x+13y-4x-3y=40-(-40)=>10y=80 => y=8to find x replace y per its value in a or b and get x=-16

Normally, this is a difficult form of the equation to deal with. To change it into a more familiar form, we can do this: 4x + 3y = 0 3y = -4x y = (-4/3)x

4x + 12y = 4(x + 3y)

The solution of 4x plus 3y -9 and x -3 is; 5x+3y-3.

y intercept: x = 0 3y = 0 y = 0 x intercept: y=0 -4x = 0 x = 0 (0,0)

2x + 3y + 4x + 9y = 2x + 4x + 3y + 9y = 6x + 12y which can be simplified to 6(x + 2y)

(1) x+y=15(2) 4x+3y=38From (1) one gets x=15 -y, put into(2)4(15-y)+3y=3860-4y+3y=3860-y=38y=22 then x=15-y=-7(-7,22) is the solution

4x - 3y = -7 Change all signs: -4x + 3y = 7 Add 4x to both sides: 3y = 4x + 7 Divide both sides by 3: y = (4/3)*x + 7/3 m = 4/3, b = 7/3